Effects of the glucagon-like peptide-1 receptor agonist liraglutide on systolic function in patients with coronary artery disease and type 2 diabetes: a randomized double-blind placebo-controlled crossover study. Issue 1 (December 2016) - Kumarathurai, Preman; Anholm, Christian; Nielsen, Olav; Kristiansen, Ole; Mølvig, Jens; Madsbad, Sten; Haugaard, Steen; Sajadieh, Ahmad
Abstract Background Patients with type 2 diabetes (T2D) and coronary artery disease (CAD) have increased risk of cardiac dysfunction. The diabetic heart is characterized by increased fatty acid oxidation and reduced glucose uptake resulting in reduced cardiac efficiency. Glucagon-like peptide-1 (GLP-1) has shown to increase myocardial glucose uptake and to improve myocardial function. We examined the effect of the GLP-1 receptor agonist, liraglutide, on the systolic function of the left ventricle (LV) in patients with T2D and stable CAD. Methods In this placebo-controlled crossover study, 41 subjects with T2D and stable CAD were randomized to liraglutide or placebo and underwent dobutamine stress echocardiography (DSE) and exercise tolerance test at beginning and end of each intervention. The primary endpoint was changes in LV ejection fraction. Secondary endpoints were exercise capacity and other measures of systolic function: wall motion score index (WMSI), global longitudinal strain (GLS) and strain rate (GLSR). Results Liraglutide, when compared to placebo, did not improve LV ejection fraction at rest (+0.54 %; 95 % CI 2.38–3.45), at low stress (+0.03 %; 95 % CI 3.25–3.32), at peak stress (+1.12 %; 95 % CI 3.45–5.69), or at recovery (+4.06 %; 95 % CI 0.81–8.93). No significant changes in WMSI were observed at any stress levels. GLS and GLSR at rest did not improve. The maximal exercise capacity estimated by metabolic equivalents was not affected by liraglutide. Conclusion In conclusion, liraglutide did not improve the systolic function of the left ventricle during DSE or the exercise capacity in patients with T2D and stable CAD. Clinical Trial Registration http://www.clinicaltrials.gov (unique identifier: NCT01595789)